3D game development with Microsoft Silverlight 3 : beginner's guide : a practical guide to creating real-time responsive online 3D games in Siliverlight 3 using C#, XBAP WPF, XAML, Balder, and Farseer Physics Engine /: beginner's guide : a practical guide to creating real-time responsive online 3D games in Siliverlight 3 using C#, XBAP WPF, XAML, Balder, and Farseer Physics Engine. (2009) - Unknown
No abstract available